Infant Safe Sleep Initiative in a Small Volume Maternity Service. Issue 4 (July 2022) - Patterson, Kimberly J.; Adams, Ellise D.; Ramieh, Charlotte
Abstract: Purpose: Despite the 2016 American Academy of Pediatrics recommendations for preventing sudden unexpected infant death, there are approximately 3, 400 sudden unexpected infant deaths annually in the United States. Modeling of safe sleep practices by nurses in the hospital influences parents' practice at home; however, safe sleep practices are not consistently modeled during the childbirth hospitalization. Methods: A quality improvement project was conducted to implement a safe sleep initiative based on the 2016 American Academy of Pediatrics recommendations for nurses caring for hospitalized infants after birth. Evaluation included testing of nurses' knowledge, infant crib audits, and nurses' evaluation of the intervention. Results: A significant improvement was found in overall nurse education scores. Crib audits demonstrated a significant improvement in the following elements: use of multiple blankets, swaddling of the infant, and parent teaching. Nursing surveys reported an increase in confidence to practice safe sleep recommendations and educate and redirect parents. Clinical Implications: Implementing a safe sleep initiative can increase nurses' knowledge, improve adherence to recommendations with modeling safe sleep practices, and increase parent awareness of safe sleep recommendations, potentially positively affecting adherence after discharge. Abstract : Safe infant sleep practices in the hospital are the foundation for safe sleep practices by parents and caregivers after hospital discharge and can decrease risk of sudden unexpected infant death. In this quality improvement project conducted in a small volume maternity service in a community hospital, details are offered about how to implement a safe infant sleep program based on recommendations from the American Academy of Pediatrics.